Anxiety and Depression Levels in Obese College Going Students - Sai P.Dhamangaonkar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
This study was carried out to find out anxiety and depression level in obese college going students. This study was conducted on 70 subjects .The DASS Questionnaire was given to all the subjects. This questionnaire contains 42 symptoms divided into depression scale, anxiety scale and stress scale .Subjects were asked to rate their symptoms according to 4 point severity scale provided in the DASS Questionnaire. The patients were classified according to DASS questionnaire scoring. Data analysis suggested, there is significant variations seen in anxiety and depression level than stress level in obese students.